POLICIES TO CONTROL PLAGUE EPIDEMIC IN SEMIRECHENSKAYA OBLAST (1900S-1910S) - Bazarbayeva Shakhsanam Muratovna (Journal Park Publishing, 2024)
This article covers veterinary policy in Semirechenskaya oblast in the early 20th century, infectious diseases prevalent among livestock (especially plague), and the activities of veterinary doctors and veterinary paramedics.
Keywords: Semiverstvo region, veterinary policy, livestock, veterinarians, veterinary paramedics.